Preventing malaria in pregnancy: a study of perceptions and policy implications in Mukono district, Uganda - Mbonye, Anthony K.; Neema, Stella; Magnussen, Pascal (Health policy and planning, 2006)
Although the efficacy of insecticide-treated nets (ITNs) in malaria prevention is well documented, the low coverage of ITNs in malaria endemic countries necessitates investigation on factors that limit access to this intervention. An exploratory study was conducted in Mukono district, Uganda, to assess perceptions and use of ITNs. Results show that malaria is perceived as a serious illness among pregnant women and children, and there is high awareness on the benefits of ITNs. However, ITNs are used by few people, mainly because of their high cost and the perception that the chemicals used to treat them have dangerous effects on pregnancy and the foetus. Other factors that influence the use of ITNs include low utilization of antenatal care, husband’s lack of interest in malaria prevention and the perception that adolescent girls and primigravidae are at a low risk of getting malaria. The policy implications of these findings include demystifying the negative perceptions on the chemicals used to treat nets and subsidizing the cost of ITNs in order to increase access to them. These findings provide important lessons for malaria control programmes that aim at increasing access to ITNs by pregnant women in developing countries.
Keywords: Malaria in pregnancy; Perceptions; Insecticide-treated nets; Uganda